Adhesion and invasion of Streptococcus pneumoniae to primary and secondary respiratory epithelial cells - Novick, Sara (Mol Med Rep, 2017)
The interaction between Streptococcus pneumoniae (S. pneumoniae) and the mucosal epithelial cells of its host is a prerequisite for pneumococcal disease development, yet the specificity of this interaction between different respiratory cells is not fully understood. In the present study, three areas were examined: i) The capability of the encapsulated S. pneumoniae serotype 3 strain (WU2) to adhere to and invade primary nasal-derived epithelial cells in comparison to primary oral-derived epithelial cells, A549 adenocarcinoma cells and BEAS-2B viral transformed bronchial cells; ii) the capability of the unencapsulated 3.8DW strain (a WU2 derivative) to adhere to and invade the same cells over time; and iii) the ability of various genetically-unrelated encapsulated and unencapsulated S. pneumoniae strains to adhere to and invade A549 lung epithelial cells. The results of the present study demonstrated that the encapsulated WU2 strain adhesion to and invasion of primary nasal epithelial cells was greatest, followed by BEAS-2B, A549 and primary oral epithelial cells. By contrast, the unencapsulated 3.8-DW strain invaded oral epithelial cells significantly more efficiently when compared to the nasal epithelial cells. In addition, unencapsulated S. pneumoniae strains adhered to and invaded the A459 cells significantly more efficiently than the encapsulated strains; this is consistent with previously published data. In conclusion, the findings presented in the current study indicated that the adhesion and invasion of the WU2 strain to primary nasal epithelial cells was more efficient compared with the other cultured respiratory epithelial cells tested, which corresponds to the natural course of S. pneumoniae infection and disease development. The target cell preference of unencapsulated strains was different from that of the encapsulated strains, which may be due to the exposure of cell wall proteins.